Error control with constrained codes (2014)
M.Ing.(Electrical and Electronic Engineering) === In the ideal communication system no noise is present and no errors will be made. However, in practice, communication is over noisy channels which cause errors in the information. There is thus a necessity for the control of these errors. Furthermore, several channels impose runlength or disparity constraints on the bit stream. Until recently, the error control on these channels was applied separately to imposing the input restrictions with constrained codes. Such a system leads to poor performance under certain conditions. and is more complex and expensive to apply than systems where the error control is an integral part of the constrained code or decoder. In this study, we firstly investigate the error multiplication phenomena of constrained codes. An algorithm is presented that minimizes the error propagation probabilities of memoryless decoders according to two criteria. Another algorithm is presented along with the first to calculate the resulting bit error probabilities. The second approach to the error control of constrained codes is the construction of combined error-correcting constrained finite-state machine codes. We investigate the known construction techniques and construct several new codes using extensions of the known techniques. These codes complement or improve on the known error-correcting constrained codes with regards to either complexity, rate or error-correcting capability. Furthermore, these codes have good error behaviour and favourable power spectral densities.